The Pintu Seribu Mosque Seen from Historical and Scientific Elements of the Concept of Lighting and Temperature - Lelly Qodariah (Postgraduate, University of Mataram, 2023)
This research aims to evaluate the aspects of lighting and room temperature in the Thousand Gate Mosque, Banten, with a focus on its historical and scientific value. Using a descriptive method, room temperature and natural lighting, which affect the comfort of mosque users, were measured and monitored. The results revealed that the lighting and room temperature in the mosque do not meet the comfort standards set in Indonesia. As a solution, additional lighting such as lamps, air conditioning, or fans are needed to optimize the room temperature. Furthermore, through interviews and observations, it was found that the Thousand Gate Mosque holds historical significance, still recognized by the local community as a place of worship and a historical symbol due to its architecture. In conclusion, improving the evaluation of lighting and room temperature is necessary to enhance the comfort for mosque users. Additionally, promoting the mosque as a historical and educational destination is crucial to appreciate and utilize its historical value to the fullest. Thus, these efforts can preserve the authenticity of the mosque and provide greater benefits to the community and visitors